A Biphasic Medium Slows Down the Transfer Hydrogenation and Allows a Selective Catalytic Deuterium Labeling of Amines from Imines Mediated by a Ru−H/D+ Exchange in D2O. Issue 23 (26th November 2018) - Ruiz‐Castañeda, Margarita; Carrión, M. Carmen; Santos, Lucía; Manzano, Blanca R.; Espino, Gustavo; Jalón, Félix A.
Abstract: The transfer hydrogenation (TH) of several aldimines has been studied using [RuCl( p ‐cymene)(dmbpy)]BF4, 1, (dmbpy=4, 4′‐dimethyl‐2, 2′‐bipyridine) as a precatalyst. Both neat water and a biphasic water/toluene mixture (w/t) have been successfully used as solvents. In the w/t medium the corresponding precursors, amine and aldehyde, were also used as substrates for a transfer hydrogenative reductive amination. Selective deuterium labeling of the resulting alkylated amines was the main goal of this work. On using D2 O the D‐content in the amine was negligible but a high level of D‐incorporation was achieved in D2 O/toluene. According to calculations, this is due to the effect of the relative rates of the hydride transfer and that of the RuH/D + exchange. The incorporation of deuterium increases with time as a consequence of the reduction in the hydride transfer rate as the substrate concentration diminishes. The recyclability assays performed reflect the importance of pH in the selectivity of the TH towards the imine or the aldehyde resulting from imine hydrolysis. Abstract : And now for something a little different : The use of a biphasic medium D2 O/toluene allows the selective deuterium incorporation in alkylated amines obtained from transfer hydrogenation from aldimines. This incorporation, which takes place by a RuH/D + exchange, is negligible in neat D2 O.